Governança corporativa: empresas familiares e o seu nível de maturidade – estudo de caso na indústria da borracha - Albuquerque, Luís Fernando Gomes de (2019)
Governance brings to companies a model of transparency and seriousness that goes beyond the physical limitations of a company. It reaches people directly and indirectly linked to the company, other entities that are involved in the business and society. Family companies are increasingly adopting the principles of corporate governance in their management. But a large chunk of these companies is still managed by intuition. Because they are representative in the economy, in the social sector and because they are great employers, this dissertation aims to measure the level of maturity of the rubber industry's family businesses. This work focused on the study in the rubber industry for this sector to be part of the researcher's life. The research methodology of this work was of the bibliographic and experimental type. Bibliographical, we sought concepts and theories of renowned authors and researchers on Corporate Governance. In the experimental type survey, a questionnaire was applied to the managers of family companies with the intention of measuring the level of maturity of these companies. We used a research from the University of Pretoria, where the authors studied the levels of maturity of the companies. The level of maturity of this research was used as a criterion to make this dissertation feasible. The results obtained with the questionnaire leads to the conclusion that family companies are knowledgeable about the products and / or services that are part of the business. Often the products and services bear the family name. However, there is a way to be worked and improved when addressing the management question